Funding growth in bank-based and market-based financial systems: evidence from firm-level data - Demirgüç-Kunt, Aslı; Maksimovic, Vojislav (Journal of Financial Economics, 2002)
We investigate whether firms’ access to external financing to fund growth differs in market-based and bank-based financial systems. Using firm-level data for 40 countries, we compute the proportion of firms in each country relying on external finance and examine how that proportion differs across financial systems. We find that the development of a country's legal system predicts access to external finance, and stock markets and the banking system affect access to external finance differently. However, we find no evidence that firms’ access to external financing is predicted by several proxies for relative development of stock markets to the development of the banking system.